Factors affecting perceived stigma in leprosy affected persons in western Nepal. - Bipin Adhikari; Nils Kaehler; Robert S Chapman; Shristi Raut; Paul Roche (Public Library of Science (PLoS), 2014)
BACKGROUND: There are various factors which construct the perception of stigma in both leprosy affected persons and unaffected persons. The main purpose of this study was to determine the level of perceived stigma and the risk factors contributing to it among leprosy affected person attending the Green Pastures Hospital, Pokhara municipality of western Nepal. METHODS: A cross-sectional study was conducted among 135 people affected by leprosy at Green Pastures Hospital and Rehabilitation Centre. Persons above the age of 18 were interviewed using a set of questionnaire form and Explanatory Model Interview Catalogue (EMIC). In addition, two sets of focused group discussions each containing 10 participants from the ward were conducted with the objectives of answering the frequently affected EMIC items. RESULTS: Among 135 leprosy affected persons, the median score of perceived stigma was 10 while it ranged from 0-34. Higher perceived stigma score was found in illiterate persons (p=0.008), participants whose incomes were self-described as inadequate (p=0.014) and who had changed their occupation due to leprosy (p=0.018). Patients who lacked information on leprosy (p=0.025), knowledge about the causes (p=0.02) and transmission of leprosy (p=0.046) and those who had perception that leprosy is a severe disease (p<0.001) and is difficult to treat (p<0.001) had higher perceived stigma score. Participants with disfigurement or deformities (p=0.014), ulcers (p=0.022) and odorous ulcers (p=0.043) had higher perceived stigma score. CONCLUSION: The factors associated with higher stigma were illiteracy, perceived economical inadequacy, change of occupation due to leprosy, lack of knowledge about leprosy, perception of leprosy as a severe disease and difficult to treat. Similarly, visible deformities and ulcers were associated with higher stigma. There is an urgent need of stigma reduction strategies focused on health education and health awareness programs in addition to the necessary rehabilitation support.